Transactions in the Field of Banking Operations: Historical and Legal Analysis (on the example of the XIX-XX centuries) (Law and Safety, 2020)
The peculiarities and legal nature of transactions in the field of banking operations from the point of view of historical and legal understanding have been studied.It has been established that the legal regulation of banking operations provided powers for each type of banking institutions only by individual transactions and a set of operations, the content of which was determined primarily by the functions of a particular type of banking institutions. However, the list of these operations, fixed in the legislation, gradually expanded as the latter improved. The main banking operations provided for each type of credit institution remained virtually unchanged, and the expansion of the number of operations was due to the emergence of additional operations, which were transformed into separate types of transactions.In general, the regulation of banking operations within the study period was multilevel, which was expressed in the adoption of laws and regulations. At the same time, most bylaws were adopted for public and small credit institutions. Regarding joint-stock commercial banks, the various instructions and orders were not sufficiently specified for them, as a result of which those institutions could act independently within their statutes. This suggests that the activities of commercial banks were insufficiently regulated in the absence of mandatory licensing of banking operations.The basic principles of state policy in the field of banking activities and banking operations have been determined.
Keywords: banking system; evolution of banking system formation; banking activity; legislation on banks and banking activity